MENJADI ARSIPARIS KOLABORATIF MELALUI PENDIRIAN iSchool: Array - Aida Safitri (Jurnal Kearsipan, 2019)
Among others, archivist should be able to provide access to information over time. But it is impossible to do so all alone. By applying literature study to several journals and books, this article aims to urge collaboration among many other recordkeeping professionals, not only archivists, through an establishment of School of Information (iSchool). Due to the growing problems of digital transformation iSchool would become a scientific hub for knowledge and insight sharing.